The Implementation of Bureaucratic Reform by the Local Government of Pinrang Regency - Azmi, Ilima Fitri; Syukur, Alam Tauhid; Amelia, Rezky (KnE Social Sciences, 2022)
Bureaucratic reform is obligatory for all government institutions, in central or local government. The eight change areas that are the focus point of bureaucratic reform are: change management, legislation improvement, organizational arrangement and strengthening, management arrangement, apparatus management system improvement, supervision strengthening, performance accountability strengthening, and quality of public services improvement. This research attempted to provide an overview of how the Pinrang Regency Government implemented the 2015–2019 Bureaucratic Reform Roadmap, and the obstacles faced in this implementation, so as to be able to provide recommendations to the Pinrang Regency Government. This research applied the policy program implementation process theory which analyzes the stimulus of a policy, the policy, the programs and the implementation. Through this analysis, some implementation gaps were identified such as: local agencies’ lack of awareness of the urgency of bureaucratic reform; differences of perception about what bureaucratic reform is, why it needs to be accomplished, and how to reform; and incorrect assumptions about bureaucratic reform. To solve these existing problems, it is recommended that the local government of Pinrang Regency conducts a thorough evaluation on the implementation of bureaucratic reform. Keywords: implementation, policy program implementation process, bureaucracy reform